Growth of Red Spinach (Amaranthus tricolor L.) Hydroponically Using POC Tomatoes and Moringa Leaves - Pranata, Sepbrie Mulia Bingah; Suparti, Suparti (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: Red spinach (Amaranthus tricolor L), one of the plants contains several important elements with high nutritional value, is liked by the community, easy to cultivate with hydroponics. Efforts to determine the growth of red spinach by administering POC as a nutrient needed by plants. The purpose of this study was to find out how red spinach plants grow in POC of a mixture of tomato extract and moringa leaf extract with the addition of coconut water hydroponically and at what concentration the most effective POC. This research was conducted at the Biology Green House FKIP UMS. Methods: this study used an experimental method with a completely randomized design (CRD) with 2 factors, namely factor 1 type of POC extract mixture and factor 2 the difference in the volume of POC so that from both factors 6 treatments were obtained with three replications for each treatment. Results: Data analysis using Two Way Anova showed that the results of the C2V2 treatment had a plant height of 2.13 cm, root length of 1.96 cm, and the highest number of leaves with 4 strands. The C1V3 treatment produced the lowest plant height, namely 1.07 cm and the C2V3 treatment produced the lowest root length, namely 0.73 cm and the C1V1, C1V3, C2V1, C2V3 treatments showed the lowest number of leaves, only 2 leaves. Conclusion: The POC of tomatoes and Moringa leaves which were given the same treatment showed that the POC of Moringa leaves were effectively used as red spinach growth nutrients.